Stock Market Reaction to Terrorist Attacks and Political Uncertainty: Empirical Evidence from the Tunisian Stock Exchange - Ben Moussa, Fatma; Talbi, Mariem (International Journal of Economics and Financial Issues, 2019)
Political uncertainty and terrorist attacks have shown a remarkable surge around the world. These events creates uncertainty by increasing the risk to invest in some countries and this adversely affects stock markets, and can lead to lower economic growth, increased cost to companies, and negative affects to the society. This study examines the impact of political instability and terrorist attacks on the Tunisian stock market using data for two sub-periods: the pre-revolution period and the period during the revolution. Using an EGARCH model, empirical evidence shows that both types of events (political and terrorist) affect the performance and volatility of the Tunindex market especially after the revolution. Indeed, political events and those linked to terrorist attacks reduce returns and increase the volatility of the stock index. However, the effect of these events on the behavior of the stock market was lower for the period before the revolution. Keywords: Political instability, terrorism, stock market return, volatility, emerging market. JEL Classifications: G11, G12, G14, C58, F31 DOI: https://doi.org/10.32479/ijefi.7968